The Quality Services to increasing visitors after New Normal in Marine Tourism Attractions in Polewali Mandar Regency - Muh. Kasim (Universitas Muhammadiyah Palu, 2024)
Visitor loyalty to tourist attractions is crucial as it maintains a stable and loyal customer base, reduces promotional costs, and increases visitor spending. Understanding factors is essential to enhancing visitor experiences and the positive reputation of tourist destinations. The purpose of this study is to examine the factors influencing visitor loyalty to tourism attractions in Polewali Mandar after the New Normal era and the Covid-19 disaster. Specifically, the study investigates the impact of reliability, insurance, tangibles, empathy, and responsiveness on visitor loyalty in the region. The findings suggest that while the quality of services provided by tourism attractions meets some expectations, there remains a discrepancy between visitor expectations and actual experiences. Despite this, the marine tourism attractions in Polewali Mandar continue to attract visitors due to their promising locations and scenic views. However, overall satisfaction with reliability, assurance, tangibles, empathy, and responsiveness is moderate, indicating there is room for improvement in service delivery at these tourism sites.